2010
DOI: 10.1577/t09-125.1
|View full text |Cite
|
Sign up to set email alerts
|

Red Snapper Reproductive Biology in the Southern Gulf of Mexico

Abstract: Sex ratio, size at maturity, reproductive periodicity, ovarian development pattern, and spawning ground data for red snapper Lutjanus campechanus from the southern Gulf of Mexico were analyzed to understand this species' reproductive biology throughout its geographical distribution. Red snapper were sampled in 1999 and 2000 from commercial fishery catches taken on Campeche Bank at depths ranging from 43 to 130 m. Overall sex ratio (male : female) and sex ratios by size-class did not differ significantly from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
31
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 15 publications
2
31
0
Order By: Relevance
“…Differences between sexes (for adults only) could also be appreciated even though we did not perform a direct comparison between adults: L. synagris, L. campechanus and O. chrysurus adult-females were bigger and heavier than adult-males. Trejo-Martínez (2011) andSámano-Zapata (2010) reported that in all three Snapper species males reach sexual maturity earlier and at smaller sizes than females. Mean gonadosomatic index was even bigger in males (3.30±0.23-0.50±0.03%) of Ocyurus chrysurus than in females (2.30±0.13-0.50±0.03%) suggesting that there is an important deviation of surplus energy canalized to reproduction in males.…”
Section: Discussionmentioning
confidence: 96%
“…Differences between sexes (for adults only) could also be appreciated even though we did not perform a direct comparison between adults: L. synagris, L. campechanus and O. chrysurus adult-females were bigger and heavier than adult-males. Trejo-Martínez (2011) andSámano-Zapata (2010) reported that in all three Snapper species males reach sexual maturity earlier and at smaller sizes than females. Mean gonadosomatic index was even bigger in males (3.30±0.23-0.50±0.03%) of Ocyurus chrysurus than in females (2.30±0.13-0.50±0.03%) suggesting that there is an important deviation of surplus energy canalized to reproduction in males.…”
Section: Discussionmentioning
confidence: 96%
“…Red snapper support important commercial and recreational fisheries in Dashed curves show how a given resilience level can be met through tradeoffs between spatial and temporal diversity. (B) Potential relationships with age of reproductive traits impacting reproductive success: spawning stock biomass (SSB; a proxy for abundance), annual fecundity (blue), spawning duration as a proxy for the distribution of spawning events within a spawning season (black), and the maternal effects on egg and larval quality (red) the Gulf of Mexico and the southeastern USA, with both the Gulf and South Atlantic (SA) stocks exhibiting highly truncated age distributions (Cowan 2011 (Collins et al 1996, Woods et al 2003, BrownPeterson et al 2009, Brulé et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…The proposed reproductive terminology appears to be applicable to all fishes, from primitive to more evolved, regardless of reproductive strategy or gender. Indeed, this terminology has recently been used to describe the reproductive cycle of an elasmobranch (thornback ray: Serra-Pereira et al 2011), a freshwater teleost (threespine stickleback Gasterosteus aculeatus: Brown-Peterson and Heins 2009), and several marine teleosts (e.g., silver perch Bairdiella chrysoura: Grammer et al 2009; spotted seatrout: Lowerre- red snapper: Brown-Peterson et al 2009 andBrulé et al 2010;beardfish Polymixia lowei: Baumberger et al 2010). It is our strong hope that researchers studying fish reproduction will adopt this terminology for the purpose of improving communication among those in fish-related disciplines.…”
Section: Discussionmentioning
confidence: 99%